Assessment of the Impacts of Coastal Flooding using Remote Sensing and GIS: A Review - ADEYEMI, Adedoyin Benson; BABAYEMI, Enoch Oluwaferanmi; OLATUNJI, Kolawole Benjamin-Franklin (ABUAD Journal of Engineering and Applied Sciences, 2025)
Around the world, coastal regions are frequently densely populated, heavily farmed, unduly reliant on groundwater, and undergoing a rise in coastal development. The cumulative consequences of climate change make the vulnerability of coastal communities to floods an urgent concern. By using remote sensing and GIS techniques, it is possible to accurately anticipate future inundation scenarios, identify locations that are prone to floods, and measure the degree of flooding. This study aims to demonstrate the critical role that GIS and remote sensing play in expanding our knowledge of the effects of coastal flooding. Three case studies within Nigeria were selected and considered: Lagos Coastal Area, Niger Delta Coastal Region, and Calabar Coastal Zone. The case studies, which examined individual articles, assessed the effects of coastal flooding and demonstrated the versatility and intricacy of GIS and remote sensing in delivering useful information. Results from the reviewed studies indicate that the highly susceptible areas cover a larger percentage of the coastal regions in Nigeria, with approximately 41% highly susceptible area coverage in Lagos and 63% highly susceptible coverage in Delta. In the Calabar region, floods were recorded to have a significant negative influence on the socioeconomic and environmental well-being of the people living in the region. The study made future research directions promising by highlighting the combination of machine learning and cutting-edge technologies to improve the efficiency of GIS and remote sensing in coastal flooding assessments.